2011
DOI: 10.1111/j.1365-313x.2011.04781.x
|View full text |Cite
|
Sign up to set email alerts
|

ABERRANT PANICLE ORGANIZATION 2/RFL, the rice ortholog of Arabidopsis LEAFY, suppresses the transition from inflorescence meristem to floral meristem through interaction with APO1

Abstract: SUMMARYThe temporal and spatial control of meristem identity is a key element in plant development. To better understand the molecular mechanisms that regulate inflorescence and flower architecture, we characterized the rice aberrant panicle organization 2 (apo2) mutant which exhibits small panicles with reduced number of primary branches due to the precocious formation of spikelet meristems. The apo2 mutants also display a shortened plastochron in the vegetative phase, late flowering, aberrant floral organ id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
202
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(212 citation statements)
references
References 56 publications
9
202
0
1
Order By: Relevance
“…Similar activities for F-box proteins have been reported previously in yeast and mammals (Muratani and Tansey, 2003). UFO orthologs in petunia and rice [DOUBLE TOP (Souer et al, 2008) and ABER-RANT PANICLE ORGANIZATION1 (APO1; Ikeda-Kawakatsu et al, 2012), respectively] have been shown to physically interact with their respective LFY orthologs (ABERRANT LEAF AND FLOWER and RFL/APO2, respectively), suggesting that the dependence of LFY on F-box regulation for some of its activity is conserved across angiosperms.…”
Section: Regulation Of Floral Homeotic Genes By Lfymentioning
confidence: 57%
“…Similar activities for F-box proteins have been reported previously in yeast and mammals (Muratani and Tansey, 2003). UFO orthologs in petunia and rice [DOUBLE TOP (Souer et al, 2008) and ABER-RANT PANICLE ORGANIZATION1 (APO1; Ikeda-Kawakatsu et al, 2012), respectively] have been shown to physically interact with their respective LFY orthologs (ABERRANT LEAF AND FLOWER and RFL/APO2, respectively), suggesting that the dependence of LFY on F-box regulation for some of its activity is conserved across angiosperms.…”
Section: Regulation Of Floral Homeotic Genes By Lfymentioning
confidence: 57%
“…LFY and APETALA1 (AP1) induce each other's expression to initiate flower primordium emergence and morphogenesis 7,8 . Unlike their counterparts in Arabidopsis 9 , rice AP1-like and LFY-like genes are involved in inflorescence meristem specification [10][11][12] . Instead, OsMADS1/LEAFY HULL STERILE1 (LHS1), an E-class gene, functions similarly to LFY and AP1 in determining floral meristem initiation and specification 13,14 .…”
mentioning
confidence: 99%
“…Orthologs of RA2 and RA3 (but not RA1) are found in the rice genome, but their functions are unknown. The rice genes ABERRANT PANICLE1 (APO1) and APO2 are orthologs of the Arabidopsis genes UNUSUAL FLORAL ORGANS (UFO) and LEAFY (LFY), respectively, and they negatively regulate the shift to SM identity (10)(11)(12). In Arabidopsis and other eudicot species, UFO and LFY promote determinate floral meristem identity (10).…”
mentioning
confidence: 99%